Requirements for Human Respiratory Syncytial Virus Glycoproteins in Assembly and Egress from Infected Cells - Melissa Batonick; Gail W. Wertz (Advances in Virology)
Human respiratory syncytial virus (HRSV) is an enveloped RNA virus that assembles and buds from the plasma membrane of infected cells. The ribonucleoprotein complex (RNP) must associate with the viral matrix protein and glycoproteins to form newly infectious particles prior to budding. The viral proteins involved in HRSV assembly and egress are mostly unexplored. We investigated whether the glycoproteins of HRSV were involved in the late stages of viral replication by utilizing recombinant viruses where each individual glycoprotein gene was deleted and replaced with a reporter gene to maintain wild-type levels of gene expression. These engineered viruses allowed us to study the roles of the glycoproteins in assembly and budding in the context of infectious virus. Microscopy data showed that the F glycoprotein was involved in the localization of the glycoproteins with the other viral proteins at the plasma membrane. Biochemical analyses showed that deletion of the F and G proteins affected incorporation of the other viral proteins into budded virions. However, efficient viral release was unaffected by the deletion of any of the glycoproteins individually or in concert. These studies attribute a novel role to the F and G proteins in viral protein localization and assembly.